Current state of sentinel lymph nodes for women with endometrial cancer. Issue 3 (1st February 2019) - Rossi, Emma C
Abstract : Sentinel lymph node (SLN) biopsy has been investigated as an alternative to conventional pelvic and para-aorticlymphadenectomy for the surgical staging of endometrial cancer. Clinical trials have established the accuracy of sentinel nodes in the detecting metastatic disease. Novel advancements in tracers from the historically favored blue dyes and radio labeled colloids to near infrared imaging of fluorescent dyes has improved the ability to detect sentinel nodes and increased options for surgeons. The uterine cervix has been shown to be a feasible and accurate injection site for tracer, though the potential for under-evaluation of the para-aortic nodes remains a controversy, particularly for high-risk cancers. Additionally, sentinel node evaluation provides qualitatively different information than traditional staging techniques by identifying lymph nodes outside of traditional sampling locations and through the identification of very low volume meta static disease implants, such as isolated tumor cells. It is unclear how this altered staging information should be interpreted, guide the prescription of adjuvant therapy and its impact on long term clinical outcomes such as recurrence and survival. In this review we will discuss the evidence that has supported the use of the SLN technique in the staging of endometrial cancer, the options for surgical technique and the implications of managing the results of staging pathology.